PENGARUH SIKAP DAN NORMA SUBJEKTIF TERHADAP NIAT BELI DAN KEPUTUSAN PEMBELIAN - Aryadhe, Trisdayana; Suryani, Alit; Sudiksa, Ida Bagus (E-Jurnal Manajemen, 2018)
ABSTRACT The increasingly fierce competition of the motorcycle industry demands every producer to be sensitive to the advancement of the times, technology and changing needs or tastes of its consumers. The purpose of this study is to test and know the truth of previous research on the effect of attitude variables on buying intention, subjective norms of purchase intention and purchase intention to consumer purchasing decision of Honda Scoopy motorcycle in Denpasar City. Sampling method using non-porbability sampling through purposive sampling technique with sample size of 120 respondents. Data collection was done by spreading the questionnaire directly in Denpasar City. Data analysis technique used is PLS (Partial least square). The result of research indicate that attitude and subjective norm have positive and significant effect to buying intention, as well as relationship between buying intention to purchase decision showing the same result that is positive and significant. Keywords : attitude, subjective norm, purchase intention, purchase decision.